Treatment options for Leber hereditary optic neuropathy - Povilaitytė , I.; Liutkevičienė , R. (Neurologijos seminarai, 2018)
Leber hereditary optic neuropathy (LHON) is the most common hereditary optical neuropathy caused by primary mutations in mitochondrial DNA. LHON manifests as opticnerve atrophy and loss of central vision. In about 70% of LHON cases three major mutations in mitochondrial DNA: 11778G>A/ND4, 3460G>A/ND1 and 14484T>C/ND6 are detected. Literature also describes more than 18 novel mtDNA mutations associated with LHON and the dysfunction of mitochondrial electron transport chains. Due to this dysfunction, ATP synthesis decreases and the level of oxidative stress in ganglion cells of the retina increases, which leads to cell degeneration and apoptosis.In this article, we review the main manifestations of Leber hereditary optic neuropathy and its treatment options.
Keywords: Leber hereditary optic neuropathy; etiology; diagnosis; treatment